2005
DOI: 10.1097/01.alc.0000158840.07475.97
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ethanol Withdrawal???Induced Anxiety-Like Behavior During Later Withdrawals by Treatment of Early Withdrawals With Benzodiazepine/??-Aminobutyric Acid Ligands

Abstract: Single-dose administration of drugs that enhance or diminish activity at benzodiazepine-gamma-aminobutyric acid- receptors during earlier withdrawals reduced or potentiated, respectively, anxiety-like behavior during later, drug-free withdrawals. These results support the potential of the novel strategy of using prophylactic therapy administered during early withdrawals to ameliorate symptoms of later withdrawals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 50 publications
8
50
0
3
Order By: Relevance
“…To determine if the repeated LPS/withdrawal and the TNFa/ withdrawal protocols share sensitivity to flumazenil inhibition of withdrawal-induced anxiety-like behavior after the repeated withdrawal and repeated stress/withdrawal protocols Knapp et al, 2004Knapp et al, , 2005, rats were treated with flumazenil (5 mg/kg, 2 ml/kg i.p. ; Roche, Basel, Switzerland) or 0.5% carboxymethylcellulose vehicle 30 min before each of the two weekly doses of LPS (250 m; i.p.)…”
Section: Flumazenil Treatment Before Repeated Lps Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if the repeated LPS/withdrawal and the TNFa/ withdrawal protocols share sensitivity to flumazenil inhibition of withdrawal-induced anxiety-like behavior after the repeated withdrawal and repeated stress/withdrawal protocols Knapp et al, 2004Knapp et al, , 2005, rats were treated with flumazenil (5 mg/kg, 2 ml/kg i.p. ; Roche, Basel, Switzerland) or 0.5% carboxymethylcellulose vehicle 30 min before each of the two weekly doses of LPS (250 m; i.p.)…”
Section: Flumazenil Treatment Before Repeated Lps Administrationmentioning
confidence: 99%
“…), but not during withdrawal from the 5 days of ethanol diet. This dose of flumazenil was chosen based upon effectiveness in previous studies to diminish the adaptive change induced by the repeated withdrawal protocol (Knapp et al, , 2005 and the repeated stress/ withdrawal protocol . Subsequently, social interaction was measured in controls and drugtreated groups as noted above.…”
Section: Flumazenil Treatment Before Repeated Lps Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments previously blocked the reduced social interaction seen following this repeated ethanol cycling (Overstreet et al, 2003a(Overstreet et al, , b, 2004bKnapp et al, 2004bKnapp et al, , 2005. Treatment with the these drugs during the initial repeated withdrawal cycles prevented the stressinduced reduction in social interaction induced 3 days after removal from the multiple-withdrawal protocol (Figure 4).…”
Section: Effect Of Selected Drugs Administered During Repeatedmentioning
confidence: 87%
“…Previous work demonstrated that a CRF 1 -receptor antagonist, a 5-HT 1A -receptor agonist, and the benzodiazepine receptor antagonist administered during repeated withdrawals prevent withdrawal-induced anxiety-like behavior (Knapp et al, , 2005Overstreet et al, 2003bOverstreet et al, , 2004a. This inhibitory drug action is proposed to relate to blockade of the cumulative adaptive change induced by the repeated withdrawals (Overstreet et al, 2003a(Overstreet et al, , b, 2004a.…”
Section: Discussionmentioning
confidence: 99%